IRAK signalling in cancer - Rhyasen, G W (Br J Cancer, 2015)
Innate immune signalling has an essential role in inflammation, and the dysregulation of signalling components of this pathway is increasingly being recognised as an important mediator in cancer initiation and progression. In some malignancies, dysregulation of inflammatory toll-like receptor (TLR) and interleukin-1 receptor (IL1R) signalling is typified by increased NF-κB activity, and it occurs through somatic mutations, chromosomal deletions, and/or transcriptional deregulation. Interleukin-1 receptor-associated kinase (IRAK) family members are mediators of TLR/IL1R superfamily signalling, and mounting evidence implicates these kinases as viable cancer targets. Although there have been previous efforts aimed at the development of IRAK kinase inhibitors, this is currently an area of renewed interest for cancer drug development.